Kencenderungan Kelompok Muda Untuk Berwirausaha Berdasarkan Faktor-faktor Personal - Santosa, Ratna Muljani; Christian, Michael (Jurnal Pengabdian dan Kewirausahaan, 2017)
One of the acceleration of a country's economic growth can be supported by the participation of creative and risk-taking labor force groups. However, sometimes the courage does not run in balance with creativity. Therefore, the tendency of younger groups to start independent businesses is often constrained by internal factors such as personal principles and unwillingness to take risks. Personal attitudes will depend on individual perceptions formed through life experience, learning, observation of others and other things. This study aims to see the entrepreneurial intention by the factors of propensity to act (creativity, self-control, norms and attitudes) of young groups to act in realizing independent entrepreneurship. Quantitative research with questionnaire instrument using the Statistical Package for Social Science (SPSS) 22 application, this study used multiple regression analysis on the error rate of 5%. This research explains about partial entrepreneurship intention by individual creativity in young group. On the other hand, the entrepreneurial intention partially is not known by social norms and the courage to take risks in young groups. Subsequent studies may use more sample quantities to explain the likely outcomes. In addition, further research can also use a description of the choices on the item being asked to give more precision to the factor of courage in taking the risk of entrepreneurship.Keywords: entrepreneurship, propensity to act, intention